simpify (x^m+n)^2×(2^n+p)^2×(x^p+m)
Attachments:
![](https://hi-static.z-dn.net/files/d63/385661024e9893fc51f6527b0e53a2b8.jpg)
Answers
Answered by
0
Answer: (x^m+n)^2(p+2^n)^2(x^p+m)
Step-by-step explanation:
So we have to simplify (x^m+n)^2×(2^n+p)^2×(x^p+m).
1. (x^m+n)^2(2^n+p)^2(x^p+m)
2{Apply exponent rule: a^m b^m=(ab)^m, assuming a\ge 0, b\ge 0 (x^m+n)^2(p+2^n)^2=((x^m+n)(p+2^n))^2
=((x^m+n)(p+2^n))^2(x^p+m)
=(x^m+n)(p+2^n))^2(x^p+m)
Please mark me as brainliest...
If there is a mistake please let me know and I will try to fix it.
I hope this helps!
Similar questions
Social Sciences,
3 months ago
Math,
3 months ago
Political Science,
3 months ago
Chemistry,
6 months ago
Chemistry,
6 months ago
Science,
1 year ago
Science,
1 year ago